DIELECTRIC PROPERTIES OF INDUSTRIAL POLYMERCOMPOSITE MATERIALS - Ali, Nadia A; Noori, Farah T Mohammed; Hussin, Sinaa I (Al-Nahrain Journal of Science, 2010)
Frequency and temperature dependence of dielectric constant ( ) and dielectric loss ( ) inpure epoxy resin and polymer composites with glass fiber are studied in the frequency range40Hz-110 MHz and in the temperature range (25-150)0C.The experimental results show that andincreased with the addition of glass fiber in epoxy resin. The value of ( ) decreased with increasingfrequency which indicates that the major contribution to the polarization comes from orientationpolarization .Dielectric loss peaks were also observed in the composite materials at hightemperature due to Tg of epoxy .The value of ( ) increased with increasing temperature, and is dueto greater freedom of movement of the dipole molecular chains within the epoxy at hightemperature.